Analysis of the Pension System in Ukraine: Realities and International Experience - Zalubovska, S. S.; Melnyk, V. A. (Statistics of Ukraine, 2016)
Analysis of legal aspects involved in the pension system and studies of demographic indicators measuring this system capacity has been increasingly important due to the critical role of the pension system as part of broader system for social security. The article contains analysis of the pension system in Ukraine and the direction of its reforms, especially the reforms of solidarity system of pensions, prevailing now in Ukraine. Demographic and economic indicators that have impact on the pension level in Ukraine are studied: pension age and average life expectancy, employed population aged 15-70. It is emphasized that the increasing employment in the Ukrainian economy has no effect for the pension level, because the number of people in the pension age has been increasing by higher rates that the employment number. The indicators of minimal and maximal pensions, cost of living, minimal and maximal wage in Ukraine are studied. A comparative analysis of demographic indicators and pension indicators in Ukraine and selected countries of Europe and other world is made. The analysis shows wide gap between Ukraine and the above countries, including new EU member countries, by pension level. The living standard of pensioners is estimated by net pension income, derived as a percentage of net average earnings. For the individual income, which equals to the average, it is derived as the replacement rate. Results of pension modeling for different levels of individual earnings are presented. The conclusion is made from the analysis that the central problems of the Ukrainian pension system are low pensions of the majority of the population in the pension age and the imbalanced budget of the Ukrainian Pension Fund.